Alice Waters, with Bob Carrau and Patricia Curtan, and illustrations by Ann Arnold: Fanny at Chez Panisse - A Child’s Restaurant Adventures with 46 Recipes - Davidson, J (Petits Propos Culinaires, 1992)
Alice Waters, with Bob Carrau and Patricia Curtan, and illustrations by Ann Arnold: Fanny at Chez Panisse - A Child’s Restaurant Adventures with 46 Recipes: Harper Collins, New York, 1992: 133 pp, illustrations on almost every page, index, US23.00 (20.00 through 31 December 1992).